Physicochemical Parameters and Fish Assemblages in the Downstream River of a Tropical Hydroelectric Dam Subjected to Diurnal Changes in Flow - Lee, Nyanti; Noor Iskandar, Noor Azhar; Soo, Chen Lin; Ling, Teck Yee; Sim, Siong Fong; Jongkar, Grinang; Tonny, Ganyai; Lee, Karen Suan Ping (Hindawi Publishing, 2018)
Te downstream river of the tropical Batang Ai Dam is experiencing diurnal fow fuctuation due to power generation operation. Tree samplings were conducted to collect the water quality and fsh assemblage data and one sampling was conducted to study the hydrological characteristics of the downstream river. Te results show that the downstream river is extremely shallow and moves slowly when the power generation is halted and no water is discharged from the powerhouse. Signifcant correlations between river fow and pH, dissolved oxygen (DO), total suspended solids (TSS), and fve-day biochemical oxygen demand (BOD5) indicated that those parameters were infuenced by the water discharge regulation. Fish abundance was low in upstream segment but it gradually increased as distance from the dam increased and was signifcantly correlated with DO. Fish diversity in the downstream river was infuenced by the river depth and chlorophyll a concentration. Te most abundant fsh species, Cyclocheilichthys apogon, exhibited a negative allometric growth pattern, while Hampala macrolepidota and Hemibagrus planiceps exhibited an isometric growth pattern. Fulton’s condition factor () values for 89.4% of H. planiceps were ≤1, indicating poor to extremely poor conditions.